Evolution of managers' opinions on usability of different resources for developing competitive advantages = Zarządzanie zasobami w zmieniającym się środowisku - Bielski, Ireneusz (Zielona Góra: Faculty of Economics and Management Press)
Nowadays, in order to survive and operate on the market, enterprises need to focus on developing competitive advantages as well as on using all the available methods one of which being entrepreneurial strategy. This strategy provides the possibility to achieve success on the market by being able to detect the opportunities that appear in the constantly changing business environment and take advantage of them using the available resources. Effectiveness of the accepted strategy is determined by selection of the resources that are to be used for developing competitive advantages.
Keywords: strategia przedsiębiorczości; przewaga konkurencyjna; zasoby firmy; zasoby ludzkie; otoczenie biznesu; nowoczesne przedsiębiorstwo; entrepreneurial strategy; competitive advantages; resources of the company; business environment; modern enterprise